Effect of small-sided games and high-volume continuous endurance running on the condition of adolescent female handball players in the pre-season - Belka, J.; Hulka, K.; Safar, M. (Medicina dello Sport, 2022)
BACKGROUND This study assesses whether high-volume continuous endurance training (HVT) still has a place in the preparatory period in handball training or whether this run could be replaced by small-sided games (SSGs).